2013
DOI: 10.1039/c3dt50147g
|View full text |Cite
|
Sign up to set email alerts
|

Models of the iron-only hydrogenase: a comparison of chelate and bridge isomers of Fe2(CO)4{Ph2PN(R)PPh2}(μ-pdt) as proton-reduction catalysts

Abstract: Reactions of Fe2(CO)6(μ-pdt) (pdt = SCH2CH2CH2S) with aminodiphosphines Ph2PN(R)PPh2 (R = allyl, (i)Pr, (i)Bu, p-tolyl, H) have been carried out under different conditions. At room temperature in MeCN with added Me3NO·2H2O, dibasal chelate complexes Fe2(CO)4{κ(2)-Ph2PN(R)PPh2}(μ-pdt) are formed, while in refluxing toluene bridge isomers Fe2(CO)4{μ-Ph2PN(R)PPh2}(μ-pdt) are the major products. Separate studies have shown that chelate complexes convert to the bridge isomers at higher temperatures. Two pairs of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 66 publications
23
68
0
Order By: Relevance
“…2 and 3, the molecular structures of both complexes contain a butterfly diiron cluster coordinated by propanedithiolate, five terminal carbonyls and a monophosphine ligand. The [15], but shorter than those found in natural enzymes (2.55-2.62 Å ) [2,3] and other diiron complexes [25][26][27][28]. The average Fe-C bond distances of the substituted Fe (1.768 Å for 2 and 1.764 Å for 3) are slightly shorter than those of the unsubstituted Fe (1.796 Å for 2 and 1.781 Å for 3) due to the monophosphine having stronger electron-donating properties than CO [29,30].…”
Section: X-ray Crystal Structuresmentioning
confidence: 98%
“…2 and 3, the molecular structures of both complexes contain a butterfly diiron cluster coordinated by propanedithiolate, five terminal carbonyls and a monophosphine ligand. The [15], but shorter than those found in natural enzymes (2.55-2.62 Å ) [2,3] and other diiron complexes [25][26][27][28]. The average Fe-C bond distances of the substituted Fe (1.768 Å for 2 and 1.764 Å for 3) are slightly shorter than those of the unsubstituted Fe (1.796 Å for 2 and 1.781 Å for 3) due to the monophosphine having stronger electron-donating properties than CO [29,30].…”
Section: X-ray Crystal Structuresmentioning
confidence: 98%
“…[1][2][3][4][5][6] Two key features have been identified and targeted: [7][8][9][10][11][12][13][14][15][16][17] (1) a rotated geometry along the Fe-Fe axis favoring the formation of a terminal hydride intermediate and (2) an amino group that can be protonated, in the dithiolate bridge, serving as a proton shuttle to the metal center (Scheme 1). On that basis, Rauchfuss and co-workers synthesized [Fe 2 (μ-adt H )(CO) 2 -(κ 2 -dppv) 2 ] {adt H = (SCH 2 ) 2 NH, dppv = (PPh 2 ) 2 C 2 H 2 }, a FeFe-H 2 ase model that catalyzes the electrochemical reduction of a weak acid (pK a ≈ 15 in MeCN) to H 2 at an unprecedented TOF value of 58,000 s -1 with an overpotential of 0.5 V.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Sun and co‐workers found that a toluene solution of diiron adt complex Fe 2 { μ ‐adt N(Pr‐ n ) }(CO) 6 with dppm was refluxed to afford only a bridge complex Fe 2 { μ ‐adt N(Pr‐ n ) }(CO) 4 ( μ ‐dppm) . Moreover, Hogarth, Song, and we reported that a series of PNP‐chelate diiron complexes Fe 2 ( μ ‐xdt)(CO) 4 { κ 2 ‐(Ph 2 P) 2 NR} were prepared by the carbonyl substitutions of Fe 2 ( μ ‐xdt)(CO) 6 (xdt = pdt, edt, adt) with ligands (Ph 2 P) 2 NR (PNP) using Me 3 NO assistance and UV irradiation …”
Section: Introductionmentioning
confidence: 99%